Traços do discurso religioso fundador de Glorinha/RS : suas histórias e aspectos religiosos - Knobeloch, Márcio Darlan Rosa (2008)
To trace historical aspects about the town of Glorinha/RS, we started from the reflections of its people, doing the approach from the concept to the ethnic, thinking about the "a historicity of the speech process". Thus, we verified approaches and contradictions depending on the point of view. This way, connected to ethnical issues is the notion of identity. Those ethnic notions about identity might include people in a community or create label impositions taking them apart, not respecting the living with different people. Therefore, we tried to approach these facts to a historic and religious reality of the town of Glorinha/RS, starting with the Guarani, follwed by Portugese-Brazilians arrived in the 18th century imposing its culture, the Roman Catholic religion, after all its "modus vivendi". Added to them the Azoreans arrived in the 17th century also. This way, how has been the speech of the majority of Portuguese descendents and the minority of other ethnics, such as the black people that arrived like slave and the immigrate Germans and their descendents? Among the Portuguese-Brazilian there are the new-Christians, who are ascendants from Jewish-Iberian and were forcedly converted to the Catholicism. Portuguese, Azorean, black people and German brought in their cultural luggage their religiosity, because their religious phenomenon could happen in the community of the religions and where it usually taken place, as well as a personal way, with syncretism or not. Finally, we did an analysis about the field research done with followers of denominations founded in the downtown of Glorinha/RS, what might have a relation with the founded speech of the history of Glorinha/RS and the religious denominations presented in this town. The questionnaire was gently offered by the GDIREC Gestando o Diálogo Inter-religioso e o Ecumenismo, established in the Social Directory in the Religion Area, UNISINOS, taking the first three questions. The analysis of the responses was enriched with dialogs before and after the interviews and curiosities that raise questions added to the theory, including the speech mechanisms, that don t take as values about each religious faith or ethnia before.